Who Votes Without Identification? Using Individual‐Level Administrative Data to Measure the Burden of Strict Voter Identification Laws. Issue 2 (7th June 2021) - Henninger, Phoebe; Meredith, Marc; Morse, Michael
Abstract : Legal disputes over laws that require certain forms of identification (ID) to vote mostly focus on the burden placed on people who do not possess ID. We contend that this singular focus ignores the burden imposed on people who do possess ID, but nonetheless cannot access it when voting. To measure this alternative conception of burden, we focus on Michigan, which allows anyone who lacks access to ID to vote after signing an affidavit. A sample of affidavits filed in the 2016 presidential election from a random set of precincts reveals that about 0.45 percent of voters lacked access to ID. Consistent with our broader conception of the burden of voter ID laws, nearly all voters who filed an affidavit were previously issued a still‐active state ID. Importantly, we show minority voters were about five times more likely to lack access to ID than white voters. We also present survey evidence suggesting that people who live in states where voters are asked to show ID, as in Michigan, are more likely to incorrectly believe that access to ID is required to vote than are people who live in states that do not ask voters to show ID.